The Effect of Conflict on Ukrainian Refugees' Return and Integration - Joop Adema; Cevat Giray Aksoy; Yvonne Giesing; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2023)
During 2022, about eight million Ukrainians were displaced from Ukraine due to the Russian invasion. Whether these individuals will return holds great significance for Ukraine's reconstruction and is pivotal in shaping integration strategies in host countries. We used Facebook ads to recruit a panel of Ukrainian refugees in Europe, starting in June 2022. Six waves carried out in 2022 and 2023 allow us to examine the causal impact of local conflict intensity on refugees' return intentions and integration. We find that less than 10% of Ukrainian refugees express a desire to permanently settle abroad. While the duration of time spent abroad leads to a higher proportion of refugees being employed, it does not diminish their intentions to return. Conflict intensity in one's home municipality decreases current return intentions, but it has only a small impact on plans to return once safety is restored.
Keywords: D74; F22; J24; 330; conflict; Ukraine; migration; refugees; return migration